Sosialisasi Teori Dan Microteaching Penerapan Pmr Dalam Kooperatif Tipe STAD SMP Negeri 7 Padangsidimpuan - Rahmayanti, Yuni; Arifitriana, Wirna; Samosir, Khairunnisa (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
The partners of this Community Service Program are students from SMP Negeri 7 Padangsidimpuan. The partners' problems are as follows: 1) Students' difficulty in understanding mathematics subjects, 2) Students' low interest in studying mathematics, 3) Students' perspective which considers learning mathematics to be difficult and boring, 4) Low ability and skills of some teachers in presenting teaching material as interesting as possible and 5) Students' economic limitations to take part in tutoring in terms of studying mathematics material outside of school. To address these problems, we are interested in holding a Community Partnership Program (PKM) in the field of educational services. This program will help students face and solve problems related to learning mathematics. Therefore, students in the process of learning activities need study guidance by experts to overcome problems related to learning mathematics. Thus, this activity was carried out as an effort to erase the impression that mathematics is a difficult and boring lesson (Math Phobia) so that it becomes an easy and fun lesson (Math is Fun). It is hoped that all programs implemented will lead to improving mathematics learning outcomes. The results achieved through this activity were the formation of a teacher working group (KKG) with 2 to 5 members each, based on the distribution of teaching class levels. The teachers' knowledge and skills regarding cooperative learning models combined with mathematical approaches have increased from the "fair" to "good" category.